Superradiance of J-aggregates: correspondence between infinite disordered chain and regular chain of finite length - Ratner, M.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The radiation decay of excitons in a slightly disordered molecule chain is considered. The degree of disordering dictates the excitonic state length that determines the enhancement of the decay rate Г (superradiance). Г was calculated versus disordering degree and temperature and compared with the case of a regular chain where the length of excitonic state is determined by the chain length, N. For every degree of disordering, the value of N was found that provides practically the same decay rate as a function of temperature.